Agile methodologies between software development and music production: an empirical study - Ciancarini, Paolo; Ergasheva, Shokhista; Farina, Mirko; Mubarakshin, Damir; Succi, Giancarlo (Frontiers in Computer Science, 2023)
Over the past 20 years agile methodologies revolutionised Information Technology, offering tremendous opportunities for the development of Software Engineering as an independent discipline. More specifically, agile methodologies contributed to enhancing the effectiveness and the speed of the production process as well as to improving the productivity and motivations of software developers organized in high performing teams. The agile philosophy can be and has been applied in different contexts and across several domains. This work analyses the relationship between Agile methodologies used by software engineers and the practices pursued by musicians in their daily lives. Our findings suggests that collaborative, strongly planned software development life cycle models (such as Waterfall, V-model, iterative, and Spiral) are not adequate models to describe the daily practices of musical composers. This is because their work requires a lot of flexibility, which such models intrinsically lack, because they are oriented to ensuring some form of monitorable progress. Interestingly, our findings also show that nine out of 12 Agile Principles are consciously or unconsciously followed by musicians in their practices. This suggests that there are some deep connections between these two prima facie different fields, which are both very creative. Even though our findings await replication, possibly with larger statistical samples, they contribute to open up a new strand of research in the field.